Avaliação clínico-ultrassonográfica e patológica de lesões da veia epigástrica superficial cranial de bovinos de leite - Douglas Rodrigues do Nascimento Gonzaga (2019)
Cranial superficial epigastric vein lesions (ESVS) present an increased incidence in dairy cattle in Minas Gerais and are associated with the daily puncture of this blood vessel for the application of synthetic oxytocin. The clinical, ultrasonographic and pathological aspects of the lesions are still unknown and studies on the negative influence of these lesions on blood flow and milk production are scarce, as well as the possibility of thrombi originated in this vessel can cause lesions in other organs. Thus, this study determined that animals receiving synthetic oxytocin rarely present compromised systemic health even though they can present phlebitis and periflebitis, evidenced in the clinical and ultrasonographic examination. These lesion are characterized as a chronic inflammatory process and fibrosis, evidenced in these exams by greater distance between the skin and the blood vessel with larger subcutaneous thickness and a greater thickness of the vessel wall. However, this variation did not contribute statistically to the reduction of vessel diameter, presence and velocity of blood flow. In this way it can be affirmed that no damages were observed to the irrigation and drainage of the mammary gland. On the other hand, VESC thrombosis, evidenced in a significant number of animals, is an important factor for their survival and is now recognized as a source of emboli for multicentric lesion in cows in Brazil. The data generated in this study will have immediate practical application in clinical routine and clinical imaging and pathological diagnosis, and elucidated some aspects not yet known of this alteration, allowing the appropriate therapeutic measures to be applied for its control and prevention.